2016
DOI: 10.24042/ajpm.v7i1.29
|View full text |Cite
|
Sign up to set email alerts
|

Modifikasi Model Pembelajaran Gerlach dan Ely Melalui Integrasi Nilai-Nilai Keislaman Sebagai Upaya Meningkatkan Kemampuan Representasi Matematis

Abstract: This study aims to determine whether the modification of learning models Gerlach and Ely through the integration of Islamic values can improve the ability of mathematical representation of learners. This research uses Pre-Experimental Design method with one-group pretest-posttest type. The prerequisite analysis test was performed by Liliefors test for normality and F test for homogeneity, then the data were analyzed by using N-Gain test and correlated t-test. The results of the analysis show that the mathemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 1 publication
0
4
0
5
Order By: Relevance
“…We selected this model for the following reasons: First, it has proven valuable since it was proposed and is regarded as being sufficiently comprehensive for examining the design and implementation of learning [27]. Second, although first proposed in 1971, the model remains relevant in diverse research settings, including the face-to-face context [28,29] and online T&L more recently [30]. The model is regarded as sufficiently broad and flexible for pedagogical design and evaluation.…”
Section: Data Codingmentioning
confidence: 99%
“…We selected this model for the following reasons: First, it has proven valuable since it was proposed and is regarded as being sufficiently comprehensive for examining the design and implementation of learning [27]. Second, although first proposed in 1971, the model remains relevant in diverse research settings, including the face-to-face context [28,29] and online T&L more recently [30]. The model is regarded as sufficiently broad and flexible for pedagogical design and evaluation.…”
Section: Data Codingmentioning
confidence: 99%
“…Meanwhile, grade VII MTs Hidayatullah Batakte stated that there was a category of having completed learning, this was seen from the percentage of classical completeness which showed that there were 85.7% of students who had completed learning. One way to form noble character in learning mathematics is to design learning that is integrated with Islamic values [10], [11]. Coupled with hots-based questions can help students towards higher-order thinking skills and try to find solutions creatively so that new things are better and useful for their lives [12].…”
Section: Description Of the Assessment Phasementioning
confidence: 99%
“…Wulandari & Kristiawan, 2017). Untuk mewujudkan pembelajaran yang bermuatan nilai-nilai karakter lembaga pendidikan berperan sangat penting (Hazra & Banerjee, 2019;Paul, 2017;Yusnita, Masykur, & Suherman, 2016). Sehingga, sebagai lembaga pendidikan, di Madrasah Tsanawiyah diperlukan suatu pendekatan pendidikan nilai yang berbasis karakter.…”
Section: Pendahuluanunclassified